Agroecology and Sustainable Development in Africa - Kangama, Dr. Cheick Oumar (RA Journal of Applied Research, 2021)
The term agroecology is not new, since it first appeared in scientific literature in the 1930s. In recent years, it seems to have enjoyed increasing success. It constitutes a new sustainable path for rural development and adaptation to climate change. This study will allow us to assess the impacts of this mode of production and agroecological production techniques.